The role of glycated hemoglobin (HbA1c) and serum lipid profile measurements to detect cardiovascular diseases in type 2 diabetic patients (South East Asia Journal of Public Health, 2016)
Patients with diabetes are considered to be at more risk of dyslipidemia and hypertension, hence targets for cardiovascular diseases. This study describes the possible role of Glycated Hemoglobin (HbA1c) and serum lipid profile as a biomarker in the detection of cardiovascular diseases. A cross-sectional study was carried out on 54 (33 males and 21 females) type 2 diabetes (T2DM) patients at Ayub Teaching Hospital (ATH), Abbottabad and Mardan Medical Complex (MMC), Mardan, Khyber Pukhtunkhwa (KP), Pakistan. The control group comprised of 20 (13 males and 7 females) healthy human samples. The patients had significantly higher (p